2017
DOI: 10.1007/s00464-017-5561-6
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic radical antegrade modular pancreatosplenectomy for left-sided pancreatic cancer using the ligament of Treitz approach

Abstract: Lap-RAMPS using the ligament of Treitz approach is feasible and extremely helpful in performing minimally invasive, curative resection for well-selected left-sided PC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
35
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(44 citation statements)
references
References 13 publications
8
35
0
1
Order By: Relevance
“…This study clari ed that LRAMPS is technically safe and feasible procedure in well-selected patients with PC in the distal pancreas. [19].Our series with 10 cases showed a morbidity rate of 50.0%, and the PF rate of 30.0%, similar to what have been reported in the literature [5][6][7][8][9][10][11].Even the operation more complicated, the LRAMPS didn't increase the risk of complications but with the advantages related to minimal-access surgery, such as less intraoperative blood loss, faster recovery. [19].…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…This study clari ed that LRAMPS is technically safe and feasible procedure in well-selected patients with PC in the distal pancreas. [19].Our series with 10 cases showed a morbidity rate of 50.0%, and the PF rate of 30.0%, similar to what have been reported in the literature [5][6][7][8][9][10][11].Even the operation more complicated, the LRAMPS didn't increase the risk of complications but with the advantages related to minimal-access surgery, such as less intraoperative blood loss, faster recovery. [19].…”
Section: Discussionsupporting
confidence: 85%
“…[19]. Our series with 10 cases showed a count of retrieved lymph nodes of 15 (range, [13][14][15][16][17][18][19][20][21],and the R0 resection rate of 100.0%, similar to what have been reported in the literature [5][6][7][8][9][10][11].So whether LRAMPS could achieve better oncological outcomes than laparoscopic conventional DPS or similar oncological outcomes as open RAMPS need more randomized controlled test to con rm. No study to date has shown improved overall survival between RAMPS and standard DP [21][22][23].…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…This procedure was adopted by minimally invasive pancreatic surgeons, which perform laparoscopic or robotic RAMPS, with great preliminary results (6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%